2016
DOI: 10.5604/17322693.1208196
|View full text |Cite
|
Sign up to set email alerts
|

Cell reactions and immune responses to photodynamic therapy in oncology

Abstract: Photodynamic therapy (PDT) is a noninvasive, highly selective method for the treatment of diseases characterized by uncontrolled cell proliferation. It was clinically approved more than 30 years ago. PDT involves the selective uptake of a photosensitizer (PS) by neoplastic tissue, which is able to produce reactive oxygen species (ROS) upon irradiation with visible or near-infrared (NIR) light. ROS induce destruction of target cells and damage of tumor-associated vasculature and activate an antitumor immune res… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
16
0
1

Year Published

2016
2016
2023
2023

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 26 publications
(17 citation statements)
references
References 0 publications
0
16
0
1
Order By: Relevance
“… 12 , 13 In recent years, some researchers have found that PDT shows efficacy by activating local specific immunity. 14 , 15 Brotosik et al found that PDT resulted in apoptosis of epidermal keratinocytes and Langerhans cells. 16 However, there have been no clinical studies to date on the clinical mechanism of PDT in vitiligo.…”
Section: Discussionmentioning
confidence: 99%
“… 12 , 13 In recent years, some researchers have found that PDT shows efficacy by activating local specific immunity. 14 , 15 Brotosik et al found that PDT resulted in apoptosis of epidermal keratinocytes and Langerhans cells. 16 However, there have been no clinical studies to date on the clinical mechanism of PDT in vitiligo.…”
Section: Discussionmentioning
confidence: 99%
“…As known to all, three main mechanisms by which PDT mediates tumor destruction are now to be defined, namely direct tumor‐cell killing, microvascular collapse, inflammatory and immune responses ( Figure ) . In the first case, PS agents are preferentially taken up and retained by tumor cells, and induce direct cytotoxic effects on tumor cells in close proximity upon irradiation . This could be attributed to irreversible photodamage to important subcellular targets (e.g., plasma membrane, mitochondria) through oxidation of lipids, proteins and amino‐acids by ROS.…”
Section: Antitumor Mechanism Of Nir Light Triggered Pdtmentioning
confidence: 99%
“…The induced cell death response is dependent on the subcellular localization of PS. A mitochondria-localized PS would likely induce an apoptotic response whereas PS that localized in lysosomes induce a necrotic or apoptotic type of response [35]. In order to enhance their therapeutic efficiency, PSs are constantly being developed and improved by conjugating them with other molecules.…”
Section: Photodynamic Therapymentioning
confidence: 99%